Self-crystallizing expansive ground reinforcement material and ground reinforcement method
Patent Information
- Application Number
- CN202210529977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-05-16
AI Technical Summary
[0003]目前,常规的填充注浆材料中主要包含水泥、高聚合物等,水泥注浆虽然可以提高土体强度和刚度,但存在耐久性差、养护周期长、不结晶、凝固收缩、后期强度低、使用寿命短等缺陷;高聚合物注浆虽然具有化学反应速度快,强度增加快、养生时间短、膨胀率高等优点,但存在后期塑性变形、疲劳变形大、单价太高等致命缺点,且水泥、高聚合物的生产、使用伴随高能耗、高二氧化碳排放等缺点,与绿色环保、可持续发展的理念不符
[0047] The self-crystallizing expansion type foundation reinforcement material of this invention, after being mixed with water, forms a slurry with good fluidity, high density, high compressive strength, and short setting time. The crystals formed after setting have high strength and good water stability, and have high impermeability, high erosion resistance, and excellent durability.
Smart Images

Figure CN115124311B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of foundation treatment materials technology, specifically a self-crystallizing expansion type foundation reinforcement material and a foundation reinforcement method. Background Technology
[0002] In the construction of roads, foundations, and geotechnical engineering projects, it is necessary to fill and reinforce the foundation, roadbed, and rock mass to meet the quality requirements of the project.
[0003] Currently, conventional filling and grouting materials mainly include cement and polymers. Although cement grouting can improve the strength and stiffness of soil, it has defects such as poor durability, long curing period, non-crystallization, solidification shrinkage, low later strength, and short service life. Although polymer grouting has advantages such as fast chemical reaction speed, fast strength increase, short curing time, and high expansion rate, it has fatal disadvantages such as large later plastic deformation, large fatigue deformation, and high unit price. Moreover, the production and use of cement and polymers are accompanied by high energy consumption and high carbon dioxide emissions, which are inconsistent with the concept of green environmental protection and sustainable development. Summary of the Invention
[0004] The purpose of this invention is to provide a self-crystallizing expansive foundation reinforcement material and a foundation reinforcement method. The self-crystallizing expansive foundation reinforcement material, after being mixed with water, forms a slurry with good fluidity, high density, high compressive strength, and short setting time. Furthermore, the crystals formed after setting have high strength and good water stability, exhibiting high impermeability, high erosion resistance, and excellent durability.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0006] On the one hand, a self-crystallizing expansion type foundation reinforcement material is provided, which, by weight, comprises:
[0007] 400-500 parts of high-alumina cement
[0008] 200-300 parts of quartz powder
[0009] 200-300 parts of diamond powder
[0010] 10-30 parts of expanding agent
[0011] Thickener 11-25 parts
[0012] 15-30 parts of dispersant
[0013] Hardening agent 10-30 parts
[0014] 15-25 parts of retarder.
[0015] Preferably, the fineness modulus of the high-alumina cement is 800-1000 mesh, which, as an alkali activator, has the characteristics of high early strength, strong resistance to salt erosion, and good water stability.
[0016] Preferably, the quartz powder has a fineness modulus of 1000-1200 mesh, which is used to improve the activity of the slurry.
[0017] Preferably, the fineness modulus of the corundum is 1000-1200 mesh, which, as the main filler material, has the effect of increasing slurry density and improving drainage and mud squeezing.
[0018] Preferably, the expanding agent includes one or more of UEA expanding agent, AEA expanding agent, and HEA expanding agent. Its function is to inhibit slurry shrinkage, avoid excessive slurry shrinkage causing volume changes that could lead to foundation cracking, and ensure interfacial bonding effect, thereby improving the foundation reinforcement effect.
[0019] Preferably, the thickener includes a first thickener and a second thickener, and by weight, the first thickener comprises 10-20 parts and the second thickener comprises 1-5 parts;
[0020] The first thickener includes a polyurethane thickener, and the second thickener includes at least two of the following: gypsum, ethoxylated sodium alkyl sulfide, sodium dodecyl sulfonate, and water-reducing agent. The thickener can improve the workability of the geopolymer slurry, prevent segregation, and improve work efficiency.
[0021] Preferably, the dispersant comprises one or two of the following: a copolymer of vinyl acetate and ethylene, a terpolymer of ethylene and vinyl chloride and vinyl silicate.
[0022] Preferably, the hardening agent comprises LiCO3.
[0023] Preferably, the retarder comprises sodium citrate.
[0024] On the other hand, a foundation reinforcement method using the above-mentioned self-crystallizing expandable foundation reinforcement material is also provided, which includes the following steps:
[0025] S1. Construction Preparation:
[0026] Based on ground-penetrating radar detection data, the longitudinal and transverse ranges and vertical depth of the foundation reinforcement area X were determined, and the reinforcement area was temporarily closed off in accordance with safe operation requirements.
[0027] S2, Hole Position Layout:
[0028] Based on the distribution of the disease, the grouting holes are arranged in a zigzag, radial, or plum blossom pattern, and the grouting hole points P are marked. The spacing between the points can be set according to the characteristics of the disease, such as 0.5-1m or 2.0-2.5m.
[0029] S3. Drilling and cleaning:
[0030] A high-efficiency electric hammer drill was used to drill at the marked point P. The drill was kept perpendicular to the working surface during drilling to avoid swaying from side to side.
[0031] After the drilling depth reaches the designed depth, the drill rod is moved up and down several times to remove waste powder, loose soil and impurities from the borehole, so as to obtain a grouting hole P1 with a diameter of 1cm. Compared with 2-5cm grouting holes, the drilling efficiency of 1cm grouting hole is higher and the labor and material costs are lower. At the same time, it can more effectively control and reduce grout leakage. Then, use a cleaning tool to clean the dust and debris in and around the grouting hole P1.
[0032] S4. Install grouting heads:
[0033] A grouting head with an outer diameter matching the grouting hole P1 is embedded in the grouting hole P1. A rigid PVC pipe with a length matching the grouting depth and a diameter matching the grouting head and grouting hole is selected to control the depth of the grouting fluid pressure release point, thereby achieving the purpose of "precise grouting".
[0034] S5. Sealing around the pipe opening:
[0035] After the grouting pipe is embedded, the expansion of the grouting head is adjusted, and the grouting head is fixed with a steel pipe.
[0036] S6. Slurry mixing:
[0037] The above-mentioned self-crystallizing and expanding foundation reinforcement material is mixed with water to obtain grouting slurry. The mass ratio of water to self-crystallizing and expanding foundation reinforcement material is (0.3-0.4):1. The mixing adopts a "dual-cylinder parallel" mixing method to improve the mixing efficiency and thus improve the overall grouting efficiency. At the same time, the "dual-cylinder parallel" mixing method makes the mixture more uniform and more thorough.
[0038] Furthermore, water level marks should be made in the mixing tank during mixing, and the mixing time should be 45-60 seconds. The mixed grout should be uniform in color, free of lumps, sediment, white powder, etc., and its fluidity should meet the grout consistency requirements. The grout should be used immediately after preparation to prevent solidification. The mixing tank used for grout preparation should be cleaned in a timely manner after each day's construction.
[0039] S7. Grouting:
[0040] Start the grouting equipment, adjust the pressure to the design pressure of 1.0-2.0 MPa, and inject the grout into the grouting hole P1. The diffusion radius R of the grout is 1-3 m.
[0041] During grouting, if the grouting pressure rises to exceed the design grouting pressure, or if the piston of the grouting equipment stops for more than 15 seconds, or if the road surface is raised, grouting should be stopped immediately, the grouting head should be pulled out, and the grouting head should be moved to the next grouting hole for grouting.
[0042] S8. Sealing of grout outlet:
[0043] Immediately seal the grout leakage hole (observation hole) during grouting with a wooden plug, and wipe the overflowing grout around the grouting hole with geotextile;
[0044] S9, Maintenance:
[0045] After grouting is completed, the grout on the ground should be washed off with high-pressure water in a timely manner; and the area to be reinforced should be cured for 0.5-5 hours. Traffic can be opened after curing is completed.
[0046] The beneficial effects of this invention are:
[0047] The self-crystallizing expansion type foundation reinforcement material of this invention, after being mixed with water, forms a slurry with good fluidity, high density, high compressive strength, and short setting time. The crystals formed after setting have high strength and good water stability, and have high impermeability, high erosion resistance, and excellent durability. Attached Figure Description
[0048] Figure 1 This is a schematic diagram showing the arrangement of the grouting holes;
[0049] Figure 2 The grouting slurry in this invention forms crystals after initial and final setting;
[0050] Figure 3 This is a cross-sectional view of the structure formed by the crystals after solidification and the solidified body in this invention.
[0051] Figure 4 The results are from radar detection before the foundation was reinforced.
[0052] Figure 5 The radar detection results are shown after the foundation has been reinforced using the foundation reinforcement method of the present invention. Detailed Implementation
[0053] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be further described below with reference to the accompanying drawings.
[0054] Example 1:
[0055] In this embodiment, 1 "part" is 1g. Therefore, by weight, the self-crystallizing expansion type foundation reinforcement material in this embodiment includes: 480g of high-alumina cement, 200g of quartz powder, 220g of corundum, 15g of UEA expansion agent, 20g of polyurethane thickener, 1g of raw gypsum, 2g of ethoxylated alkyl sulfide sodium, 18g of vinyl acetate-ethylene copolymer, 28g of hardening accelerator, and 17g of retarder.
[0056] Example 2:
[0057] The difference between this embodiment and Embodiment 1 is that, by weight, the self-crystallizing expansion-type foundation reinforcement material in this embodiment includes: 420g of high-alumina cement, 260g of quartz powder, 250g of corundum, 10g of AEA expansion agent + HEA expansion agent, 15g of polyurethane thickener, 3g of raw gypsum, 2g of ethoxylated alkyl sulfide sodium sulfide, 15g of ethylene-vinyl chloride and vinyl silicate terpolymer, 10g of hardening accelerator, and 18g of retarder.
[0058] Everything else is the same as in Example 1, and will not be repeated here.
[0059] Example 3:
[0060] The difference between this embodiment and Embodiment 1 is that, by weight, the self-crystallizing expansion-type foundation reinforcement material in this embodiment includes: 400g of high-alumina cement, 290g of quartz powder, 200g of corundum, 28g of HEA expansion agent, 20g of polyurethane thickener, 2g of ethoxylated alkyl sulfide sodium, 3g of sodium dodecyl sulfonate, 13g of vinyl acetate-ethylene copolymer, 15g of ethylene-vinyl chloride-vinyl silicate terpolymer, 15g of hardening accelerator, and 21g of retarder.
[0061] Everything else is the same as in Example 1, and will not be repeated here.
[0062] Example 4:
[0063] The difference between this embodiment and Embodiment 1 is that, by weight, the self-crystallizing expansion-type foundation reinforcement material in this embodiment is composed of the following components: 430g high-alumina cement, 223g quartz powder, 240g corundum, 26g UEA expansion agent + AEA expansion agent + HEA expansion agent, 16g polyurethane thickener, 1g raw gypsum, 1g ethoxylated alkyl sulfide sodium sulfide, 2g dodecyl sulfonic acid, 1g water-reducing agent, 24g vinyl acetate and ethylene copolymer, 16g hardening accelerator, and 24g retarder.
[0064] Everything else is the same as in Example 1, and will not be repeated here.
[0065] Example 5:
[0066] The difference between this embodiment and Embodiment 1 is that, by weight, the self-crystallizing expansion-type foundation reinforcement material in this embodiment is composed of the following components: 448g high-alumina cement, 235g quartz powder, 208g corundum, 19g of UEA expansion agent + AEA expansion agent, 14g polyurethane thickener, 3g raw gypsum, 1g ethoxylated alkyl sulfide sodium sulfide, 1g sodium dodecyl sulfonate, 22g terpolymer of ethylene, vinyl chloride and vinyl silicate, 28g hardening accelerator, and 20g retarder.
[0067] Comparative example:
[0068] Based on mass calculations, the foundation reinforcement material used in the comparative example consists of the following components: 158g slag powder, 220g fly ash, 126g concrete powder, 365g water glass solution, 95g sodium hydroxide, 13g water-reducing agent, 11g expanding agent, 7g retarder, 3.5g defoamer, and 3.5g waterproofing agent.
[0069] The foundation reinforcement materials in Examples 1-5 and the comparative examples were all thoroughly mixed at a water-cement ratio of 0.3:1 (i.e., mass ratio of water to foundation reinforcement material = 0.3:1). The performance of the resulting foundation reinforcement slurry was tested, and the performance indicators are shown in Table 1.
[0070] Table 1 Performance Indicators of Foundation Reinforcement Grout
[0071]
[0072]
[0073] As can be seen from Table 1, the foundation reinforcement material of the present invention has significantly better fluidity than the comparative example, and its initial setting time and final setting time are both shorter than those of the comparative example, with a density of 2.5 g / cm³. 3 Therefore, when the foundation reinforcement grout of the present invention is injected into the foundation, because the density of the grout is much greater than that of water and mud, it can sink quickly, causing the water and mud in the injection hole to float to the surface and be discharged quickly, thus enhancing the grouting effect. At the same time, the compressive strength of the foundation reinforcement grout of the present invention at different time periods is significantly higher than that of the comparative example, indicating that it has excellent reinforcement performance.
[0074] Furthermore, when the foundation reinforcement material in Embodiment 1 of the present invention is used to implement the above-mentioned foundation reinforcement method, the relevant indicators are tested as follows.
[0075] like Figure 2 As shown, after the grouting slurry of the present invention fills the voids in the roadbed, it forms crystals through initial setting and final setting. It does not shrink during solidification and expands slightly during solidification. The crystal strength can reach up to 70MPa, thereby forming a homogeneous elastic modulus body with the original foundation.
[0076] Furthermore, such as Figure 3 As shown, the crystals formed after solidification can form a continuous crystalline tree system with the cemented and compacted reinforced solid. The water stability is ≥99%. Its shrinkage rate and flexural bond strength with the old road base layer both meet the relevant technical specifications for road reinforcement. It has high impermeability, high erosion resistance and excellent durability.
[0077] Furthermore, this invention also performs radar detection on the reinforced foundation:
[0078] from Figure 4 It can be seen that before reinforcement treatment, there were voids under the cement slab of the foundation and the base layer was loose and not dense. Figure 5 As can be seen, after the foundation is reinforced by the foundation reinforcement material of the present invention, there are no voids or loose areas under the foundation cement board, and the treatment effect of the disease is good.
[0079] In summary, the self-crystallizing expanding foundation reinforcement material of the present invention, after being mixed with water, forms a slurry with good fluidity, short setting time, and high strength and good water stability of the crystals formed after solidification. It also has high impermeability, high erosion resistance, and excellent durability. Therefore, the promotion of the self-crystallizing expanding foundation reinforcement material of the present invention will greatly reduce the cost of engineering projects and play a role in protecting the environment while extending the service life of road surfaces.
[0080] Where there is no conflict, the above embodiments and features described herein can be combined with each other.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A self-crystallizing, expanding foundation reinforcement material, characterized in that, By weight, it includes: 420-480 parts of high-alumina cement 260-300 parts of quartz powder 250-300 parts of diamond powder 15-28 parts of expanding agent Thickener 11-20 parts 18-30 parts of dispersant Hardening agent 10-28 parts 17-25 parts of retarder; The expanding agent includes one or more of UEA expanding agent, AEA expanding agent, and HEA expanding agent, and the thickener includes a first thickener and a second thickener, wherein the first thickener comprises 10-20 parts and the second thickener comprises 1-5 parts by weight. The fineness modulus of the high-alumina cement is 800-1000 mesh, the fineness modulus of the quartz powder is 1000-1200 mesh, and the fineness modulus of the corundum is 1000-1200 mesh. The first thickener includes a polyurethane thickener, and the second thickener includes at least two of the following: gypsum, ethoxylated sodium alkyl sulfide, sodium dodecyl sulfonate, and water-reducing agent. The dispersant includes one or two of the following: a copolymer of vinyl acetate and ethylene, a terpolymer of ethylene and vinyl chloride and vinyl silicate.
2. The self-crystallizing, expanding foundation reinforcement material as described in claim 1, characterized in that, The hardening agent includes LiCO3.
3. The self-crystallizing, expanding foundation reinforcement material as described in claim 1, characterized in that, The retarder includes sodium citrate.
4. A method for foundation reinforcement using the self-crystallizing, expandable foundation reinforcement material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Construction Preparation: Identify the area of the foundation to be reinforced and temporarily close it off. S2, Hole Position Layout: Arrange the grouting hole positions and mark the locations of the grouting holes; S3. Drilling and cleaning: Drill holes at the marked locations to obtain grouting holes with a diameter of 1 cm; and clean the dust and debris inside and around the grouting holes. S4. Install grouting heads: A grouting head with an outer diameter matching the grouting hole is embedded in the grouting hole. A rigid PVC pipe with a length matching the grouting depth and a diameter matching the grouting head and grouting hole is selected to control the depth of the grouting slurry pressure release point. S5. Sealing around the pipe opening: After the grouting pipe is embedded, the expansion of the grouting head is adjusted, and the grouting head is fixed with a steel pipe. S6. Slurry mixing: The self-crystallizing expandable foundation reinforcement material according to any one of claims 1-3 is mixed with water to obtain grouting slurry, and the mass ratio of water to self-crystallizing expandable foundation reinforcement material is (0.3-0.4):1; S7. Grouting: Start the grouting equipment, adjust the pressure to the design pressure, and inject the grouting slurry into the grouting hole; S8. Sealing of grout outlet: Seal the grout leakage hole in time during grouting, and wipe the grout overflowing around the grout hole; S9, Maintenance: After grouting is completed, the area to be reinforced will be cured, and traffic can be opened after curing is completed.
Citation Information
Patent Citations
Super-high early-strength grouting material for repairing ballastless track structure of high speed railway
CN102503310A
Super early strength type plastic expansion repair mortar and production method thereof
CN106007592A